La pervivencia de las estructuras de poder del pasado y los retos para el perfeccionamiento del Estado de derecho en América Latina a comienzos del siglo XXI - Pérez Herrero, Pedro (2006)
The essay explains why and how Latin American societies, during the period of1930 to 1980, accepted the different variants of populist regimes; why these political systems perpetuated for such a long time; what mechanisms were employed to manage internal order; why and how the destruction occurred in the decade of the 1980s; why at the beginning of the 21st century certain forms of populist-demagogicappeals in the Latin-American political panorama returned to the scene; why the State in Latin America reached such low levels of institutionalism halfway through the 20th century; why the discourse of mixed races transformed itself into the central element, capable of uniting the complex magma formed by structural heterogeneity; and why «old nationalisms» are giving way to new methods and alternative discourses about the concept of identity at the beginning of the 21st century.